2016
DOI: 10.1097/iae.0000000000001004
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure in Patients With Diabetic Macular Edema Treated With Dexamethasone Intravitreal Implant in the 3-Year Mead Study

Abstract: DEX implant demonstrated clear benefit of treatment despite increases in IOP. Sequential implants had no cumulative effect on IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
100
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 32 publications
12
100
0
6
Order By: Relevance
“…Similar results were reported by Totan et al[31] who showed a significant increase from baseline in IOP at 1 and 3 months ( p ≤ 0.04) after implant; however, these were well controlled with topical treatment. Similar to our findings, Maturi et al [30] reported a non-cumulative increase in IOP after sequential implants.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results were reported by Totan et al[31] who showed a significant increase from baseline in IOP at 1 and 3 months ( p ≤ 0.04) after implant; however, these were well controlled with topical treatment. Similar to our findings, Maturi et al [30] reported a non-cumulative increase in IOP after sequential implants.…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that re-treatment with DEX after recurrence continued to improve VA and CRT. Improvements in VA after re-treatment have also been seen in other studies [30]. …”
Section: Discussionsupporting
confidence: 62%
“…The elevated IOP is not merely the result of the added volume, but is also due to the properties of the injected drug. IOP elevation is associated with steroid therapy in general, and rates of this complication have been reported to be between 30 and 60% following IVI of triamcinolone acetonide [36-39], and between 30 and 50% following use of dexamethasone implants (Ozurdex) [40-43]. Anti-vascular endothelial growth factor (VEGF) agents have also been associated with elevated IOP, in as many as 12% of cases.…”
Section: Considerations Before Injectionmentioning
confidence: 99%
“…Medication for lowering intraocular pressure (IOP) was used at some point during the study by 41.5 and 9.1% of patients in the dexamethasone implant 0.7 mg and sham groups, respectively [52]. The proportion of patients using IOP-lowering medication remained similar in each year of the study, although 1 patient (0.3%) in each dexamethasone implant group had filtering surgery to manage a steroid-induced IOP increase [52].…”
Section: Phase III Study On the Safety And Efficacy Of Dexamethasone mentioning
confidence: 99%
“…The proportion of patients using IOP-lowering medication remained similar in each year of the study, although 1 patient (0.3%) in each dexamethasone implant group had filtering surgery to manage a steroid-induced IOP increase [52]. The profile of the IOP elevation after dexamethasone implant treatment was predictable, occurring around the second month after injection.…”
Section: Phase III Study On the Safety And Efficacy Of Dexamethasone mentioning
confidence: 99%